2016
DOI: 10.5604/20834543.1208218
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of health behaviour pattern and type D personality among dietetics students

Abstract: Wprowadzenie i cel pracy. Zachowania zdrowotne są przejawem ukształtowanej przez środowisko (np. działania edukacyjne) postawy jednostki wobec zdrowia. Oprócz czynników zewnętrznych, pewną rolę w tym procesie wydają się odgrywać również cechy osobowości. Celem pracy była ocena zachowań zdrowotnych oraz zbadanie związku pomiędzy nimi a osobowością typu D i występowaniem objawów depresyjnych u studentek dietetyki. Materiał i metody. Grupę badaną stanowiły studentki kierunku dietetyka Wydziału Zdrowia Publicznego… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…In Germany, in a study conducted in 2010 among the general population, there was a lower prevalence of distressed personality -31%, in Israel in 2011-24.1% (adult volunteers), and in Taiwan in 2013 (general population) -16% [25][26][27]. Studies conducted in Poland, mainly in selected professional groups, have shown that type D personality characterized 27.8% -45.6% of healthcare workers, 30.1% of secondary school teachers, and 43% of students who specialize in dietetics [28][29][30][31]. The frequency of type D in the general population in Poland has been estimated at 9.3% and 34.8%, depending on the study [18,32].…”
Section: Discussionmentioning
confidence: 99%
“…In Germany, in a study conducted in 2010 among the general population, there was a lower prevalence of distressed personality -31%, in Israel in 2011-24.1% (adult volunteers), and in Taiwan in 2013 (general population) -16% [25][26][27]. Studies conducted in Poland, mainly in selected professional groups, have shown that type D personality characterized 27.8% -45.6% of healthcare workers, 30.1% of secondary school teachers, and 43% of students who specialize in dietetics [28][29][30][31]. The frequency of type D in the general population in Poland has been estimated at 9.3% and 34.8%, depending on the study [18,32].…”
Section: Discussionmentioning
confidence: 99%
“…The literature also includes several studies explaining the relationship between the distressed personality (type D) and the occurrence of depression. For example, it has been shown that among dietetics students with type D personality, depression occurred significantly more often than in non-type D (43.08% vs. 7.14%; Nowak et al, 2016 ). Most of these observations are consistent with research by other authors; a similar prevalence of depressive disorders was found in Indian medical students ( N =150; 45.3%).…”
Section: Discussionmentioning
confidence: 99%
“…Człowiek aktywizuje zasoby, w sposób świadomy bądź automatyczny, w celu utrzymania równowagi organizmu w obliczu wyzwań życiowych (Hobfoll, 2006). Badane kobiety w większości charakteryzują się niskim poziomem zachowań zdro-Mandziuk (2017) indicating a low level of health behavior among nursing students (48.57% of the studied group was characterized by a low level of health behavior) (see Nowak et al, 2016). The observed correlation coefficients indicate that there is a significant correlation between an optimistic attitude towards the world and the perceived satisfaction with life and a preference for prohealth behaviors, it confirms the role of resources in shaping health present in the literature (Kelloniemi et al, 2005; Ogińska-Bulik, Juczyński, 2008;Rasmussen et al, 2009).…”
Section: Podsumowaniementioning
confidence: 99%